The urban environment in South Asia: studying the ambient air quality in a mid-sized city in Bangladesh - Hossain, Md. Monabbir; Islam, Md. Tariqul; Sikder, Sujit Kumar; Hemstock, Sarah L.; Islam, Md. Aminul; Faruquee, Mahmud Hossain; Hossain, Md. Zakir (Frontiers in Sustainable Cities, 2025)
Improving the urban environment is an urgent task in the fast-growing mid-sized cities of South Asia. Ambient air pollution is worsened by unplanned urban land use and a lack of green and waterbodies, which combined cause a rapid increase in the urban heat island (UHI) effect. This study focuses on pervasive ambient air pollution in the urban environment, primarily driven by particulate matter (PM), which presents a dire public health threat. An in-situ investigation of 48 sites in a mid-sized but fast-growing city, Mymensingh, Bangladesh, suggested that the PM2.5 concentration (118 ± 64 μg/m3) is about eight times higher than the daily average suggested by WHO (15 μg/m3). Weekdays and weekends do not show significant differences in PM generation. Geospatial analysis suggests that good air quality conditions are not found in the study area, and > 50% of people are exposed to PM10 in very unhealthy conditions (≥151 μg/m3). Traffic and commercial land cover generate the highest PM level. The monsoon climatic events control precipitation and are the most influential factor in diminishing PM concentrations. However, fast-growing mid-sized cities, like Mymensingh in Bangladesh and others throughout South Asia, are facing extreme ambient air pollution that severely impacts public health. Therefore, more action-oriented research initiatives are needed to formulate policies to control air pollution, considering local experiences, indigenous knowledge, logistics capabilities, cultural orientation, transparency, accountability, and strong collaboration, cooperation, and commitment among the public-private partnership.